Penerapan Pembelajaran Kewirausahaan Berbasis Sistem Maklun Terhadap Minat Berwirausaha - Afief Maula Novendra; Ani Setiani; Veri Aryanto; Muhammad Fadhil Syahpriyadi (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The purpose of this study was to determine how much influence entrepreneurship using maklun services has on entrepreneurial interest at SMK Medikacom. The subjects in this study were students of SMK Medikacom Bandung Accounting consisting of 2 classes, namely Accounting XI-A and Accounting XI-B classes. Data collection techniques used are observation, questionnaires, and documentation studies. To answer these problems using a quantitative approach with survey methods. The variables used in this study are Entrepreneurship Learning Using Maklun Services (X), and Entrepreneurial Interest (Y). Based on the results of research conducted by researchers on the results of entrepreneurship learning by using maklun system with descriptive test results of 3.98 with good categories, while interest in entrepreneurship shows descriptive test results of 3.97 with good categories, and entrepreneurship learning by using maklun services on entrepreneurial interest of students of SMK Medikacom there is a very strong influence with the coefficient of determination (R Square) of 81.4%. To increase entrepreneurial interest, it can incorporate entrepreneurship learning in the curriculum by collaborating with maklun system providers, holding internship programs, workshops, and practical training, as well as encouraging project development, mentoring, business simulations, competitions, and promoting the success of young entrepreneurs.